2020
DOI: 10.1186/s12909-020-02139-9
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of students’ readiness assurance test performance with team-based learning

Abstract: Background Team-based learning (TBL) is increasingly being utilized across medical fields by engaging students in small group discussions. The readiness assurance test (RAT) is an essential feature that differentiates TBL from problem-based learning (PBL) activity sequences. No publication has discussed differences in the RAT in TBL in medical schools. The purpose of this meta-analysis study was to examine the performance of learners in terms of group RAT (GRAT) and individual RAT (IRAT) scores in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…This is a necessary process however, and one with several bene ts once students work together in their teams. A meta-analysis [29], showed signi cantly improved team scores from individual scores, and noticeably so amongst nursing students. Therefore, the issue of team formation is one that needs careful consideration.…”
Section: Discussionmentioning
confidence: 99%
“…This is a necessary process however, and one with several bene ts once students work together in their teams. A meta-analysis [29], showed signi cantly improved team scores from individual scores, and noticeably so amongst nursing students. Therefore, the issue of team formation is one that needs careful consideration.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results of a meta-analysis conducted by Ngoc et al who investigated students’ performances in the GRAT phase compared to the IRAT phase. 5 …”
Section: Discussionmentioning
confidence: 99%
“…After that, students are distributed into small teams and solve the same set of MCQs through group discussion until they reach a consensus conclusion and this represents the Grouped Team Readiness Assurance Test (GRAT). 5 …”
Section: Introductionmentioning
confidence: 99%
“…This is a necessary process however, and one with several benefits once students work together in their teams as a previous study demonstrated [ 30 ]. Another meta-analysis [ 31 ], showed significantly improved team scores compared to individual scores, and noticeably so amongst nursing students. Therefore, the issue of team formation is one that needs careful consideration in improving performance.…”
Section: Discussionmentioning
confidence: 99%